2011
DOI: 10.1007/978-3-642-18120-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical Rehabilitation of Paralysed Facial Muscles: Functional and Morphological Correlates

Abstract: Reviews and critical articles covering the entire field of normal anatomy (cytology, histology, cyto-and histochemistry, electron microscopy, macroscopy, experimental morphology and embryology and comparative anatomy) are published in Advancesin Anatomy, Embryology and Cell Biology. Papers dealing with anthropology and clinical morphology that aim to encourage cooperation between anatomy andrelated disciplines will also be accepted. Papers are normally commissioned. Original papers and communications may be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 217 publications
0
1
0
Order By: Relevance
“…Previous work has suggested that excessive ''polyinnervation'' of endplates is a major factor limiting functional recovery after facial nerve repair (GuntinasLichius et al, 2005b;Angelov et al, 2007;Angelov, 2011).…”
Section: Functional Deficit Is Associated With Loss Of Glutamatergic mentioning
confidence: 97%
“…Previous work has suggested that excessive ''polyinnervation'' of endplates is a major factor limiting functional recovery after facial nerve repair (GuntinasLichius et al, 2005b;Angelov et al, 2007;Angelov, 2011).…”
Section: Functional Deficit Is Associated With Loss Of Glutamatergic mentioning
confidence: 97%